Biology and Morphometrics of Fall Armyworm, Spodoptra Frugiperda on Maize Plant (Bangladesh Journal of Agricultural Research, 2023)
The study was conducted in the laboratory of the Department of Entomology, Sher-e-Bangla Agricultural University (SAU), Dhaka, Bangladesh to observe the biology and morphometrics of fall armyworm, Spodoptra frugiperd (Lepidoptera: Noctuidae) during winter (December-February) and summer (March-May) seasons. The fall armyworm larvae were collected from the maize field of BARI, Gazipur and SAU research fields. The collected larvae were brought to the laboratory and reared on maize plant at room temperature. The female moths laid eggs in clusters under or upper surface of the maize leaf which were hatched in 4.01 and 2.45 days at winter and summer, respectively. The larvae passed through six instars with the total larval period of 29.17 and 14.80 days, respectively at winter and summer. The pupa took 17.63 days in winter and 9.34 daysin summer for emergence into adult. During winter season the longevity of female and male moths were 15.47 and 13.98 days respectively. But in summer the adult longevity for female and male was 10.03 and 8.19 days, respectively. The male-female sex ratio in winter was 1:1and 1:2 in summer. The total life cycle was completed within 64.79 days (male) and 66.28 days (female) in winter and that was 34.86 days (male) and 36.70 days (female) in summer. Larva was gradually increased in size with instars having a square shaped four black spots on 8th and 9th abdominal segments and Y-shaped line on the frons. The male pupa (16.53 mm) was slightly larger than the female (15.81 mm) with a bit longer distance between genital opening and anal slot. Body length of the adult male measured 13.75 mm and that of the female was 12.77 mm. The percent of survival was maximum at 6thinstar larval stage (94.55 %) and least survival percent was at 1st instar larval stage (79.53%). On the other hand, percent of mortality was maximum at 1stinstar larval stage (20.47%) and least mortality was at 6th instar larval stage (5.45 %).Bangladesh J. Agril. Res. 47(2): 225-239, June 2022